(3fXGe GdEKHGJ CeGe aQb GdJMcje aj EWGQ efXeI GdJLGQI GdYGdejI (B/ s - (3QVG SYjO eMeO GdLfRhQjs; (3CMeO eMeO CHh GdhaG s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3QVG SYjO eMeO GdLfRhQj (B: s, 2015)
(3jJMOO GdgOa ef gPg GdQSGdI aj OQGSI fXGe GdEKHGJ CeGe aQb GdJMcje aj GWGQ efXeI GdJLGQI GdYGdejI (B: (3MjK Ef OQGSI GdEKHGJ (B{u(32013(B} (3HUaI YGeI (B{u(32013(B} (3JJeJY HCgejI cHjQI aj eNJda GdfXe GdbGfhfjI (B{u(32013(B} (3GdOhdjI hGdhWfjI(B- :(3hef Ke JHQR CgejI OQGSI ehVhY GdEKHGJ aj GdeQGMd GdeNJdaI dJShjI GdefGRYGJ aj efXeI GdJLGQI GdYGdejI(B: (3hHUaI NGUI GdEKHGJ CeGe aQb GdJMcje (B: (3hef Ke aGf gPg GdOQGSI JYed Ydi eMGhdI GjLGO eaghe eMOO ddEKHGJ heYjGQg CeGe gPg GdaQb (B: (3hef Ke JMOjO WHjYI bhGYO GdEKHGJ heUGOQgG (B{u(32013(B} (3eY GdbGA GdVhA Ydi eG gh efUhU Ydjg aj GdJaGge hZjQg (B- : (3hCjVG JMOjO eaghe YHA GdEKHGJ heGgjI GdbQjfI GdeHOFjI(B- (3cabg LOjO(B- : (3Ke JMOjO GdeLGdjf GdELQGFj hGdehVhYj dYHA GdEKHGJ CeGe gPg GdaQb (B: (3NGUI ajeG jJYdb HTcGhi GdGfJgGc hTcGhi YOe GdGfJgGc (B: (3Ke JMOjO GdbhGYO GdJj JMOO WQb GdEKHGJ hGdJj JfXe bHhd GdCOdI CeGe aQb GdJMcje(B: (3hef CLd Gdage GdUMjM dgPg GdbhGYO GdNGUI HGdEKHGJ befG HYQV LRA JWHjbj aj gPG GdHMK jJYdb HGdEZQGb hHYV GdfeGPL GdeNJdaI ddbVGjG GdeJYdbI Hg efP fTCI efXeI GdJLGQI GdYGdejI (B: (3hYQafG ef gPG GdLGfH GdJWHjbj cja jJe JWHjb bhGYO GdGKHGJ Ydi eKd gPg GdbVGjG (B: (3eY GSJHjGf YHA heYjGQ GdEKHGJ ajgG(B- (3bVGjG GdGZQGb(B- (3hGjVG eYjGQ GdeQGLYI (B: (3GVGaI Gdi OhQ hMOhO aQb GdJMcje aj GdEKHGJ aj eKd gPg GdbVGjG(B.s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdOhdis
(3HHdjhLQGajG(B: (3UaMGJ (B743-774s
Keywords: (3GdGKHGJ ai GdGfXeI GdbGfhfjIs; (3OhQ aQb GdJMcjes; (3efXeI GdJLGQI GdYGdejIs; (3JShjI GdefGRYGJs; (3bVGjG GdGZQGbs; (3GdGZQGb ai eDJeQ GdOhMIs; (3GdeMGce GdOhdjI s; (3efXeI GdGee GdeJMOIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdOhdjs